2011
DOI: 10.1111/j.1349-7006.2011.01851.x
|View full text |Cite
|
Sign up to set email alerts
|

Fbxw7β resides in the endoplasmic reticulum membrane and protects cells from oxidative stress

Abstract: Oxidative stress has been implicated in cancer initiation and progression. Fbxw7 (also known as Fbw7, SEL‐10, hCdc4, or hAgo) is the F‐box protein subunit of an Skp1–Cul1–F‐box (SCF)‐type ubiquitin ligase complex that plays a central role in the degradation of oncoproteins such as c‐Myc, c‐Jun, Notch, and cyclin E. Fbxw7 is therefore thought to function as a tumor suppressor, and indeed the Fbxw7 gene is frequently mutated in many human malignancies. The Fbxw7 gene locus encodes three protein isoforms: Fbxw7α,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…1A). Fbw7 exists in three splice-variant isoforms, only one of which, Fbw7␤, is cytosolic (53,55). Based on mobility, the Fbw7 isoform associated with parkin is Fbw7␤, as expected.…”
Section: Parkin Associates With Fbw7␤ In Neuronsmentioning
confidence: 86%
See 2 more Smart Citations
“…1A). Fbw7 exists in three splice-variant isoforms, only one of which, Fbw7␤, is cytosolic (53,55). Based on mobility, the Fbw7 isoform associated with parkin is Fbw7␤, as expected.…”
Section: Parkin Associates With Fbw7␤ In Neuronsmentioning
confidence: 86%
“…The colocalization of Fbw7␤ and Mcl-1, presumably on the mitochondrial outer membrane, is consistent with a role for Fbw7␤ in the regulation of Mcl-1 turnover. It has been previously reported that Fbw7␤ is associated with the endoplasmic reticulum (ER) (55). However, localization experiments were carried out in nonneuronal cells ectopically expressing Fbw7␤.…”
Section: Parkin Associates With Fbw7␤ In Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fbw7β is primarily cytoplasmic protein and most abundant in brain and testis [23]. A recent study showed that Fbw7β contains a putative transmembrane domain in NH2 terminus region, and Fbw7β-deficient cells have higher sensitivity to oxidative stress [25]. Fbw7γ shows a nucleolar distribution and is expressed majorly in heart and skeletal muscle [23].…”
mentioning
confidence: 99%
“…Fbw7␣ and Fbw7␥ have been shown to be nuclear, but with Fbw7␥ being primarily nucleolar and Fbw7␣ being excluded from the nucleolus (5). Fbw7␤ is cytosolic and localizes to membrane compartments, most likely via a predicted transmembrane domain near its amino terminus (25). Since most known targets of Fbw7 are nucleoplasmic, it would be logical that they be targeted by SCF Fbw7␣ .…”
mentioning
confidence: 99%